Self-prevention of instability in a low-power microwave Ar plasma jet for biomedical applications. (20th March 2015) - Lee, H W; Kim, M S; Won, I H; Yun, G S; Lee, J K
Abstract: The behavior of a low-power microwave Ar plasma jet according to the target shape and distance is investigated. The plasma jet shows distinct behavior when it contacts a human finger or grounded metals. No plasma channel and no attraction of the jet to the human finger and metal plate are observed in contrast to low-frequency plasmas. Glow-to-arc transition does not occur even at a very small target distance (<1 mm) between a sharp metal tip and bare electrodes. It is a highly favorable property of the microwave plasma for biomedical applications. Reflection coefficient, current, electric field and electron density are investigated to find the mechanism. This unique phenomenon is caused by the characteristic of microwave frequency systems. A decrease of the target distance induces impedance mismatching leading to the reduction of net input power. It is found that the change in the geometry of the plasma jet is the dominant factor for impedance mismatching. This prevents changes in the discharge regime including glow-to-arc transition, similar to ballast. The mechanism is different from the instability prevention methods including the dielectric barrier in low-frequency systems. Insignificant electric field induced on the metal plate by the impedance mismatching can be the reason for the absence of the plasma channel. Emission intensities of reactive species of the plasma jet are almost uniform regardless of the target distance. Electrical safety and performance can be ensured by the low-power microwave plasma jet.